Identification and Analysis of Active Carotenoid Compounds From Entawak Fruit (Artocarpus Anisophyllus) - Ratnawaty, Gervacia Jenny; Indrawati, Ratih; Syari, Jajar Pramata (INTEK: Jurnal Penelitian, 2021)
— Isolation and identification of active compounds from mentawak fruit (Artocarpus Anisophyllus) used a plant determination test to determine the plant content. Furthermore, the extraction process was carried out to obtain a crude extract of carotenoid pigments by maceration method using n-hexane as solvent. Furthermore, the obtained macerate was carried out by phytochemical tests to determine the content of the active compounds. The TLC test was carried out to confirm the presence of a positive group of compounds on phytochemical screening, and to determine the chromatographic profile of the extract. The identification results showed that the phytochemicals showed that the active compounds contained in macerate were alkaloids, flavonoids, tannins and saponins. The KLT test results obtained an Rf value of 0.875. While the total carotenoid content using a spectrophotometer UV-Vis is 958 µg/ml.